Aplicação do modelo SWAT para simular vazões em uma bacia hidrográfica em Aracruz, ES - Oliveira, Laís Thomazini (2014)
The realization of hydrologic studies in watersheds comes from the need to understand the processes that control the movement of water and the impacts of the land use on water resources. The estimation of these processes and quantification of such impacts has been performed based on the use of hydrologic models. The computational model SWAT (Soil and Water Assessment Tool) was selected as the basic tool for this study in function of its objective, which aims at assessing the effects of management on water, sediment, nutrients and pesticides, and because it has been tested in different parts of the world, with satisfactory results. In this context, the present study had the objective of assessing the applicability of SWAT to estimate streamflow in an experimental watershed (MBE) with an area of 2.84 km², in Aracruz, ES. The main land use in the MBE is eucalyptus. Statistical indices calculated during the calibration and validation processes indicated that SWAT was appropriate and of satisfactory performance for the simulation of streamflows in the MBE. Besides the validation of SWAT, hypothetic scenarios of land use were simulated to assess the hydrological behavior of the watershed, including three different managements of Eucalyptus, pasture and native vegetation. Analyses of the mean streamflows, the peak streamflows associated with different return periods and minimum reference streamflows were performed. All scenarios showed sensitivity of the model to changes in the land use pasture showed the most significant responses to the increase of streamflow. The results of this study indicate that SWAT is an important tool to simulate the effect of environmental change on the hydrology of watersheds.